Alternative kidney filtration markers and the risk of major macrovascular and microvascular events, and all‐cause mortality in individuals with type 2 diabetes in the ADVANCE trial. Issue 12 (27th July 2020) - Kim, Hyunju; Wang, Dan; Chalmers, John; Jun, Min; Zoungas, Sophia; Marre, Michel; Hamet, Pavel; Harrap, Stephen; Mancia, Giuseppe; Poulter, Neil R.; Cooper, Mark E.; Woodward, Mark; et al.
Abstract: Background: Creatinine‐based estimated glomerular filtration rate (eGFR) is biased in the setting of obesity and other conditions. Alternative kidney filtration markers may be useful in adults with diabetes, but few studies examined the associations with risk of clinical outcomes. Methods: In the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) trial, we evaluated whether baseline levels and change in eGFR based on creatinine (Cr), cystatin c (Cys), β2 ‐microglobulin (B2M), eGFRCr‐Cys, and the average of three estimates (eGFRCr‐Cys‐B2M ) assessed in 7217 participants at baseline and a random sample of 640 participants at the 1‐year visit are associated with clinical outcomes. We examined associations with major macrovascular and microvascular events together and separately and all‐cause mortality using Cox regression models, adjusting for established risk factors. Results: Over a median follow‐up of 5 years, 1313 major macrovascular (n = 748) and microvascular events (n = 637), and 743 deaths occurred. Lower levels of eGFR based on all filtration markers individually and combined were associated with 1.4 to 3.0 times higher risk of major macrovascular and microvascular events (combined and separately) and all‐cause mortality. Per 30% decline in eGFRCys, eGFR Cr‐Cys, and eGFRCr‐Cys‐B2M were associated with a >2‐fold higher risk of all clinical outcomes. Conclusions: In adults with type 2 diabetes, baseline levels of eGFR based on alternative filtration markers and per 30% decline in eGFRCys, eGFR Cr‐Cys, and eGFRCr‐Cys‐B2M were associated with clinical outcomes. Measurement of alternative filtration markers, particularly B2M in adults with type 2 diabetes may be warranted. Abstract : Highlights Alternative kidney filtration markers may be particularly useful in adults with diabetes in which creatinine‐based estimated glomerular filtration rate (eGFR) is biased. Lower levels of eGFR based on all filtration markers individually and combined as well as decline in eGFRCys, eGFRCr‐Cys, eGFRCr‐Cys‐B2M were consistently associated with a higher risk of major macrovascular and microvascular events, together, and separately, and all‐cause mortality. The addition of baseline levels or change in B2M‐based eGFR improved the prediction of combined major macrovascular and microvascular events beyond creatinine. 摘要: 背景: 基于肌酐的估计肾小球滤过率(eGFR)在肥胖和其他情况中是有偏差的。替代肾滤过标记物可能对成人糖尿病患者有用, 但很少有研究分析其与临床结果风险的关系。 方法: 在糖尿病和血管疾病行动(Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation, ADVANCE)试验中, 我们评估了eGFR基线水平和基于肌酐(Cr), 胱抑素c(Cys), 表皮生长因子受体2‐微球蛋白(B2M), eGFRCr‐Cys 以及以上三者平均值(eGFRCr‐Cys‐B2M )的变化水平是否与临床结局有关, 检测了7217名参与者的基线水平和随机抽样的640名参与者的1年随访水平。我们使用Cox回归模型检验了与主要大血管和微血管事件共同发生, 各自发生, 以及全因死亡率之间的关系, 并校正了既定的危险因素。 结果: 平均随访5年, 共发生1313例大血管事件(748例)和微血管事件(637例), 743例死亡。根据所有滤过标志物单独或联合计算的低水平eGFR, 发生主要大血管和微血管事件(合并和单独发生)的风险增加1.4到3.0倍, 并且和全因死亡率相关。eGFRCys, eGFRCr‐Cys 和eGFRCr‐Cys‐B2M 每下降30%, 所有临床结果的风险增加2倍以上。 结论: 在成人2型糖尿病患者中, 基于替代滤过标志物的eGFR基线水平, 以及eGFRCys, eGFRCr‐Cys 和eGFRCr‐Cys‐B2M 下降30%与临床结局相关。可能有必要在成人2型糖尿病患者中测量替代的肾小球滤过标志物, 特别是B2M。